Adult literacy and community development: Exploring the link - Merrill D. Ewert; Peter Malvicini; Peter Clark; David Deshler (Adult Education Research Conference, 1993)
Findings, based on surveys of rural literacy directors in New York State, indicate that individual-based as opposed to community-based approaches continue to serve as the driving paradigms for rural literacy programs. Ways to link literacy education to community development efforts, remain relatively unexplored.